Optimal exogenous calcium alleviates the damage of Snow-melting agent to Salix matsudana seedlings - Li, Hui; Huang, Shenglan; Ren, Chengshuai; Weng, Xiaohang; Zhang, Songzhu; Liu, Liying; Pei, Jiubo (Frontiers in Plant Science, 2022)
Snowmelt with NaCl as the main component is widely used in the northern winter and has a greater impact on the landscape plants in the northern environment of China. Salix matsudana, as a major tree species in the northern landscape, is also under stress. However, how exogenous calcium alleviates salt stress in Salix matsudana is still unclear. In this study, fifteen treatments with combinations of three NaCl conditions (e.g., 0, 50 and 200 mmol∙L-1) and five calcium concentration gradients (e.g., 0, 100, 200, 400 and 800 mg∙kg-1) were conducted to investigate this effect by measuring the indices of growth, biomass, photosynthetic pigment, gas exchange rate and photosynthates, chlorophyll fluorescence parameters, water use efficiency (iWUE) and antioxidant enzyme activity based on a hydroponic culture experiment. The results showed that (1) the application of exogenous calcium significantly promoted the growth of Salix seedlings under sodium chloride stress. At an exogenous calcium concentration of 400 mg∙kg-1, the height and basal stem of Salix matsudana seedlings increased significantly, and the biomass of all parts reached a maximum. (2) The application of exogenous calcium to Salix matsudana seedlings under salt stress improved photosynthesis, and the photosynthetic parameters, photosynthetic pigment content and photosynthetic product synthesis of Salix matsudana showed significant changes. The photosynthetic parameters, photosynthetic pigment content and photosynthetic product synthesis of Salix matsudana seedlings showed significant changes, and the best photosynthetic level of Salix matsudana seedlings was achieved at the calcium concentration treatment level of 400 mg∙kg-1. (3) The water use efficiency of Salix matsudana was strongly influenced by NaCl stress, and at a treatment of 400 mg∙kg-1, the water use efficiency of Salix matsudana reached the peak. (4) The activities of POD, SOD and CAT enzymes of Salix matsudana seedlings under NaCl stress were measured at different concentrations of exogenous calcium. The application of exogenous calcium increased the viability and improved the growth of Salix matsudana seedlings under salt stress. In conclusion, the optimum exogenous calcium concentration for Salix matsudana seedlings was 400 mg∙kg-1. High or low concentrations of exogenous calcium did not achieve the best results in alleviating salt stress in Salix matsudana.